RECOGNITION AND AVOIDANCE OF CREDIT CARD FRAUDS USING MACHINE LEARNING - tripathy, Debashish (Journal of Advanced Research in Applied Artificial Intelligence and Neural Network; Vol 4 No 2 (2020): Journal of Advanced Research in Applied Artificial Intelligence and Neural Network, 2021)
The paper presents the utilization of multi-specialist methods for charge card related misrepresentation acknowledgment and investigation of the received methodologies for the counteraction of such cheats. A numerical model has been utilized for charge card misrepresentation recognition by contrasting distinctive smart specialists, for example, checking specialists, gathering specialists, diagnosing specialists, and announcing specialists. The charge card extortion ready messages to clients have been investigated by specialists throughout quite a while at various stages to seal the provisos and access by fraudsters to abuse it to get to clients. A multi-agent system has discovered an improvement in detecting credit card fraud cases using a multi-agent system. It is vital that credit card corporations would be able to identify fraudulent credit card transactions so that customers are not charged for transactions that they have not carried out. These issues can be addressed with Data Science and their significance, related to Machine Learning. This undertaking intends to delineate the demonstrating of an informational collection, utilizing AI to recognize Mastercard misrepresentation. The Mastercard misrepresentation discovery issue incorporates the example of Mastercard exchange history with client information that has been discovered to be a cheat. This model is utilized to perceive if another exchange is deceitful. This paper intends to identify 100% of fake exchanges and to limit invalid misrepresentation arrangements. How to cite this article: Tripathy D, Makwana C. Recognition and Avoidance of Credit Card Frauds using Machine Learning. J Adv Res Appl Arti Intel Neural Netw 2020; 4(2): 19-22